2021
DOI: 10.1038/s41565-021-01018-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle cellular internalization is not required for RNA delivery to mature plant leaves

Abstract: Rapidly growing interest in nanoparticle-mediated delivery of DNA and RNA to plants requires a better understanding of how nanoparticles and their cargoes translocate in plant tissues and into plant cells. However, little is known about how the size and shape of nanoparticles influences transport in plants and use of their cargoes, limiting development and deployment of nanotechnology in plant systems. Here, we employ nonbiolistically delivered DNA-modified gold nanoparticles (AuNP) spanning various sizes (5 -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 77 publications
(84 reference statements)
3
76
0
Order By: Relevance
“…Thus, the SPc could promote the delivery of ds- MIRNA into both plant roots and protoplasts. Nanoparticles used for nucleic acid delivery in plants include mesoporous silica nanoparticle (MSNs), single walled carbon nanotubes (SWNTs), DNA-modified gold nanoparticles (AuNP), DNA nanostructures and layered double hydroxide nanosheets (LDH), and these nanoparticles are mainly used to deliver plasmid DNA, dsRNA and siRNA by leaf injection [ 24 ]. One publication has reported the efficient DNA/dsRNA delivery in Arabidopsis through the root application, and the dendrimer-delivered DNA/dsRNA can pass through the cell wall of the Arabidopsis root cap and root hair into root tissues [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the SPc could promote the delivery of ds- MIRNA into both plant roots and protoplasts. Nanoparticles used for nucleic acid delivery in plants include mesoporous silica nanoparticle (MSNs), single walled carbon nanotubes (SWNTs), DNA-modified gold nanoparticles (AuNP), DNA nanostructures and layered double hydroxide nanosheets (LDH), and these nanoparticles are mainly used to deliver plasmid DNA, dsRNA and siRNA by leaf injection [ 24 ]. One publication has reported the efficient DNA/dsRNA delivery in Arabidopsis through the root application, and the dendrimer-delivered DNA/dsRNA can pass through the cell wall of the Arabidopsis root cap and root hair into root tissues [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…These representative nanoparticles include dendrimer [ 19 ], clay nanosheet [ 20 ], carbon nanotube [ 18 , 21 ], gold nanoclusters [ 22 ], carbon dot [ 23 ], etc. Nano-delivery systems have exploited the high degree of control over morphology and surface functionalized groups, the diverse conjugation chemistries available for cargo conjugation, and the permeability through plant tissues to overcome the biological barriers [ 24 ]. These advancements in nanotechnology have suggested a great potential for the safe and highly efficient delivery of biomolecules such as miRNA, CRISPR-Cas, and RNAi into plant cells, and it is expected to be a promising method for overcoming the limitations of miRNA delivery [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that post internalization into plant cells, AuNPs are transported from 1 cell to another via plasmodesmata along with accumulation occurring inside the plant cell wall ( Zhang et al, 2022 ). However, as evidenced from the characterization studies, the PC formed on VAuNPs and the resultant increased hydrodynamic size is likely to be responsible for the reduced toxicity and rate of internalization, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…DNA has been delivered successfully to spinach, tobacco, watercress, and Arabidopsis using chitosan-wrapped single-walled carbon nanotubes, suggesting that this could be a general mechanism applicable to different plants [79]. In addition, it was demonstrated that nanoparticles can also carry short interfering (si)RNA into plants as a carrier to exert the gene silencing effect, and delivery of siRNA does not seem to require the nanocarriers to enter plant cells, but only needs them to be released in the apoplast to function [80]. It is foreseeable that with the application of nanotechnology in cucumber in the future, the in-depth study of safety screening markers, and the continuous optimization of CRISPR/Cas9 technology, the problems currently plaguing researchers will be solved gradually.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%